Changes in Serum Calcium, Albumin and Alkaline Phosphatase Levels of Postmenopausal Women (Community Based Medical Journal, 2019)
A case-control cross-sectional study was carried out to observe the changes in serum calcium, albumin and alkaline phosphatase levels of postmenopausal women compared to their premenopausal counterparts. This is to enable us ascertain the relative risk of developing osteoporosis in postmenopausal women in Bangladesh. One hundred and eighteen (118) apparently healthy females (59 premenopausal=control and 59 postmenopausal=case) were selected for the study. The study was carried out in the Department of Biochemistry, Mymensingh Medical College in cooperation with the Department of Gynecology, Mymensingh Medical College Hospital and Community Based Medical College Hospital Bangladesh during the period from January to December 2009. Data were collected through clinical evaluation from pre-selected questionnaires. Fasting venous blood samples were taken for laboratory investigations. Serum calcium and albumin was determined using colorimetric method and enzymatic end point method was used to determine serum alkaline phosphatase levels. Statistical significance of difference between two groups were evaluated by using Student's unpaired 't' test with the help of SPSS software package. The results showed statistically significant decrease in serum calcium and albumin (p